2011
DOI: 10.1074/jbc.m111.253450
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of Ser-129 Phosphorylation on Interaction of α-Synuclein with Synaptic and Cellular Membranes

Abstract: Background:The majority of ␣-synuclein is phosphorylated at serine 129 in Lewy bodies. Results: The membrane association of PD-linked mutant ␣-synuclein, but not wild-type ␣-synuclein, was increased by serine 129 phosphorylation. Conclusion: Pathological serine 129 phosphorylation regulates membrane accumulation of mutant ␣-synuclein. Significance: The relationship of serine 129 phosphorylation to pathogenic aggregation of normal and mutant ␣-synuclein may be governed by distinct effects on phosphoprotein memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 47 publications
0
45
0
Order By: Relevance
“…Although purified recombinant ␣-syn readily associates with synthetic membranes without additional factors (30 -34), there is compelling evidence that ␣-syn distribution is highly dynamic and regulated by membrane and cytoplasmic components as follows. (i) Dissociation of ␣-syn from synaptosome membranes is significantly augmented by cytosolic proteins (9,35). (ii) Purified A30P ␣-syn has impaired binding to synthetic lipids (36 -39) but shows normal compartmentalization in vivo (9).…”
Section: Discussionmentioning
confidence: 99%
“…Although purified recombinant ␣-syn readily associates with synthetic membranes without additional factors (30 -34), there is compelling evidence that ␣-syn distribution is highly dynamic and regulated by membrane and cytoplasmic components as follows. (i) Dissociation of ␣-syn from synaptosome membranes is significantly augmented by cytosolic proteins (9,35). (ii) Purified A30P ␣-syn has impaired binding to synthetic lipids (36 -39) but shows normal compartmentalization in vivo (9).…”
Section: Discussionmentioning
confidence: 99%
“…Not only has the function of Ser(P)-129 ␣-syn modification eluded explanation, but the stage at which this modi- fication occurs is also unclear. There is some evidence that suggests that ␣-syn can also be phosphorylated post-fibrillization (14,15,45,55), perhaps as an effort to clear aggregated ␣-syn (56), which is consistent with Ser(P)-129 ␣-syn accumulation during proteasome inhibition and elevated autophagymediated ␣-syn degradation with PLK2 overexpression (16,57). Because of the overall lack of consensus across these many studies, further confounded by variations in the extent of ␣-syn phosphorylation and potential off-target effects of overexpressed kinases and ␣-syn mutants, we generated highly pure phosphorylated recombinant ␣-syn to examine its biophysical and biological properties.…”
Section: Discussionmentioning
confidence: 70%
“…Membrane Binding Properties of Monomeric Ser(P)-129 ␣-syn-We previously characterized the membrane binding of purified WT and PD-linked mutant ␣-syn to presynaptic membranes isolated from ␣-syn-deficient mouse brain (4,16). However, the impact of ␣-syn phosphorylation at its carboxyl-terminal domain, the primary pathological post-translational modification, though distal to the amino-terminal membrane binding domain, is unknown.…”
Section: Generation and Purification Of Ser(p)-129 ␣-Syn-plk2mentioning
confidence: 99%
“…Indeed, a prior study demonstrated that phosphorylation at Ser-129 reduced the affinity of ␣-synuclein to membranes in vitro (24). However, we should be careful about this notion as another in vitro study failed to show the perturbing effect of phosphorylation on its membrane-bound conformation (43), and a biochemical approach using synaptosomal membranes showed a lack of modifying effect of phosphorylation on membrane binding of WT ␣-synuclein (44).…”
Section: Phosphorylation and ␣-Synucleinmentioning
confidence: 92%